Competition shapes the landscape of X-chromosome-linked genetic diversity - Buenaventura, T; Bagci, H; Patrascan, I; Graham, JJ; Hipwell, KD; Oldenkamp, R; King, JWD; Urtasun, J; Young, G; Mouzo, D; Gomez-Cabrero, D; Rowland, BD; et al. (Nature Research, 2024)
X chromosome inactivation (XCI) generates clonal heterogeneity within XX individuals. Combined with sequence variation between human X chromosomes, XCI gives rise to intra-individual clonal diversity, whereby two sets of clones express mutually exclusive sequence variants present on one or the other X chromosome. Here we ask whether such clones merely co-exist or potentially interact with each other to modulate the contribution of X-linked diversity to organismal development. Focusing on X-linked coding variation in the human STAG2 gene, we show that Stag2variant clones contribute to most tissues at the expected frequencies but fail to form lymphocytes in Stag2WTStag2variant mouse models. Unexpectedly, the absence of Stag2variant clones from the lymphoid compartment is due not solely to cell-intrinsic defects but requires continuous competition by Stag2WT clones. These findings show that interactions between epigenetically diverse clones can operate in an XX individual to shape the contribution of X-linked genetic diversity in a cell-type-specific manner.